Senior High School Student Financial Literation Categorization, DoFamily and School Matters? An Evidence from Indonesia (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
Financial literacy is indispensable to provide knowledge about financial management. For high school students, financial literacy can be used as a foundation for financial management. The existence of financial literacy is an important aspect for managing money from an early age so that education about financial literacy is an aspect that needs to be given to high school students.This research has a novelty that it is able to analyze important factors that need to be considered to students about important financial literacy factors. This study involved 146 research samples using factor analysis. The results showed two essential factors in financial literacy towards high school students: daily financial management and investment. The most crucial factor is day-to-day financial management. This research is able to produce an elaboration of the critical factors that need to be taught to high school students.